2011
DOI: 10.1510/icvts.2011.265553
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for aspergilloma: time trend towards improved results?

Abstract: Surgery of aspergilloma has been renowned to be technically challenging and has a high complication rate. We have already demonstrated an improved outcome as a result of a reduction in complex cases related to history of tuberculosis. In this paper we will evaluate whether this time trend has continued during recent years. Initial presentation and postoperative outcome of 33 patients who underwent surgical treatment between 1998 and 2009 were reviewed and compared with two previous reports (group 1: 55 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
1
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 15 publications
5
49
1
5
Order By: Relevance
“…When performed, surgery appeared relatively safe with no reported mortality, and was well tolerated with few complications, in keeping with multiple contemporary studies where mortality rates of <1% were reported. [17][18][19][20][21] Without surgery, mortality was high (5.1%) and comparable to previous studies. [6][7][8][9][10] Our study population was relatively young and predominantly male.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…When performed, surgery appeared relatively safe with no reported mortality, and was well tolerated with few complications, in keeping with multiple contemporary studies where mortality rates of <1% were reported. [17][18][19][20][21] Without surgery, mortality was high (5.1%) and comparable to previous studies. [6][7][8][9][10] Our study population was relatively young and predominantly male.…”
Section: Discussionsupporting
confidence: 86%
“…It has the benefits of prevention of lifethreatening haemoptysis, eradication of the pyogenic component and probable prolongation of life. [15][16][17][18][19][20][21] Although surgical resection is considered curative, it is not possible in every patient, for a variety of physiological and technical reasons. Such reasons may include poor physical condition, severe comorbidity, poor pulmonary reserve, extensive lung involvement or inability to localise the bleeding site.…”
mentioning
confidence: 99%
“…With better surgical techniques, treatment outcomes have improved in recent years [130]. Procedures include bullectomy, segmentectomy, sublobar resection, wedge resection, lobectomy, pleurectomy, pneumonectomy.…”
Section: Follow-upmentioning
confidence: 99%
“…В последние годы по мере улучшения хирурги ческой техники исходы лечения улучшаются [130]. Сегодня возможны буллэктомия, сегментэктомия, сублобарная резекция, краевая резекция, лобэкто мия, плеврэктомия, пульмонэктомия.…”
Section: клинические рекомендацииunclassified